Nucleic acid cancer vaccines targeting tumor related angiogenesis. Could mRNA vaccines constitute a game changer? - Tadic, Srdan; Martínez, Alfredo (Frontiers in Immunology, 2024)
Tumor related angiogenesis is an attractive target in cancer therapeutic research due to its crucial role in tumor growth, invasion, and metastasis. Different agents were developed aiming to inhibit this process; however they had limited success. Cancer vaccines could be a promising tool in anti-cancer/anti-angiogenic therapy. Cancer vaccines aim to initiate an immune response against cancer cells upon presentation of tumor antigens which hopefully will result in the eradication of disease and prevention of its recurrence by inducing an efficient and long-lasting immune response. Different vaccine constructs have been developed to achieve this and they could include either protein-based or nucleic acid-based vaccines. Nucleic acid vaccines are simple and relatively easy to produce, with high efficiency and safety, thus prompting a high interest in the field. Different DNA vaccines have been developed to target crucial regulators of tumor angiogenesis. Most of them were successful in pre-clinical studies, mostly when used in combination with other therapeutics, but had limited success in the clinic. Apparently, different tumor evasion mechanisms and reduced immunogenicity still limit the potential of these vaccines and there is plenty of room for improvement. Nowadays, mRNA cancer vaccines are making remarkable progress due to improvements in the manufacturing technology and represent a powerful potential alternative. Apart from their efficiency, mRNA vaccines are simple and cheap to produce, can encompass multiple targets simultaneously, and can be quickly transferred from bench to bedside. mRNA vaccines have already accomplished amazing results in cancer clinical trials, thus ensuring a bright future in the field, although no anti-angiogenic mRNA vaccines have been described yet. This review aims to describe recent advances in anti-angiogenic DNA vaccine therapy and to provide perspectives for use of revolutionary approaches such are mRNA vaccines for anti-angiogenic treatments.